Why language is not Enough - Dohn, Nina Bonderup; Kjær, Christopher (Language at Work - Bridging Theory and Practice, 2008)
For many larger organisations, increased globalization means that employees, collaborators and customers are distributed throughout the world. This requires a focus within the organisation on the continuing competence development of people from all three groups, in order to make it possible for them to perform competently in their daily work.